Electrostatic charge image developing toner, image forming method, and image forming apparatus

The acrylic polymer-based toner formulation addresses charging and hot offset issues by balancing resin polarity and elasticity, enabling low-temperature fixation and reducing image adherence.

JP2025017044APending Publication Date: 2025-02-05KONICA MINOLTA INC

Patent Information

Application Number
JP2023119913
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-02-05

Smart Images

  • Figure 2025017044000001_ABST
    Figure 2025017044000001_ABST
Patent Text Reader

Abstract

To provide an electrostatic charge image developing toner which can form an image less likely to cause adhesion due to charging caused by contact with each component of an image forming apparatus, has high low-temperature fixability, and is less likely to cause hot offset.SOLUTION: An electrostatic charge image developing toner includes a binder resin in a toner base particle. The binder resin includes a polymer having a constituent unit represented by general formula (1) in the figure and a constituent unit represented by a specific formula). In general formula (1), R1 represents a hydrogen atom or a methyl group, and R2 represents a hydrocarbon group with an alicyclic structure in which the number of carbon atoms is from 6 to 12 inclusive.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a toner for developing an electrostatic image, an image forming method, and an image forming apparatus. [Background technology]

[0002] After the image formed by the toner for developing electrostatic images is fixed on the recording medium, it is conveyed while contacting many conveying rollers and is discharged. At this time, the output image may become charged due to contact with the conveying rollers or other members of the image forming apparatus. The charging of the image causes electrostatic sticking between the image and other recording media. The sticking of the image may cause an obstacle during post-processing such as varnishing or lamination, or may cause the generation of defective products that cannot be subjected to these post-processing processes.

[0003] In particular, when the printing speed is increased, the image is likely to be discharged from the image forming apparatus before the charge leaks, and the above-mentioned problems due to the charging of the image tend to occur significantly. Also, when an image is formed on a recording medium having high insulating properties such as a resin film or stone paper, the above-mentioned problems due to the charging of the image tend to occur significantly.

[0004] Patent Document 1 describes that a toner using a resin obtained by copolymerizing a (meth)acrylic monomer having a cyclic structure has a low polarity of the resin, and therefore the change in electrostatic charge caused by moisture in the air is small.

[0005] In order to increase the speed of image formation, it is necessary to improve the low-temperature fixing property of the toner. Patent Document 2 describes that a toner using a resin obtained by copolymerizing a (meth)acrylic monomer having a long-chain alkyl group has excellent low-temperature fixing property because the side chain (long-chain alkyl group) is easily crystallized. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2000-089508 A [Patent Document 2] JP 2014-130243 A Summary of the Invention [Problem to be solved by the invention]

[0007] The resin having an alicyclic structure described in the cited document 1 has low polarity. Therefore, it is expected that if a toner containing such a resin is used, charging due to contact with a conveying roller or the like is unlikely to occur, and an image that is unlikely to cause the above-mentioned charging problems can be formed. However, according to the findings of the present inventors, a resin having an alicyclic structure has low elasticity characteristics because the bulky alicyclic structure makes it difficult for the polymer chains to become entangled. Therefore, a toner containing such a resin is likely to cause hot offset. In addition, a resin having an alicyclic structure generally has a high glass transition temperature. Therefore, a toner containing such a resin does not have high low-temperature fixability.

[0008] On the other hand, the resin having a long-chain alkyl group described in the cited document 2 can improve the low-temperature fixability of the toner. However, the resin having a long-chain alkyl group has low polarity, is easily crystallized, and has a small molecular momentum, so that the dielectric loss tangent (tan δ) is low. Therefore, a toner containing such a resin is likely to cause charging of the image due to contact with a conveying roller or the like. In addition, the resin having a long-chain alkyl group is easily crystallized and polymer chains are unlikely to be entangled, so that the elasticity characteristics are low. Therefore, a toner containing such a resin is likely to cause hot offset.

[0009] The present invention has been made in consideration of the above problems, and has an object to provide a toner for developing electrostatic images that is capable of forming images that are less susceptible to sticking caused by charging due to contact with each component of the image forming apparatus, and that has high low-temperature fixing properties and is less susceptible to hot offset, an image forming method that uses the toner for developing electrostatic images, and an image forming apparatus that forms images using the toner for developing electrostatic images. [Means for solving the problem]

[0010] In order to achieve the above object, one aspect of the present invention relates to a toner for developing electrostatic images as set forth in the following items [1] to [7]. [1] A toner for developing electrostatic images, comprising a toner base particle containing a binder resin, The toner for developing electrostatic images, wherein the binder resin contains a polymer having a constitutional unit represented by the following general formula (1) and a constitutional unit represented by the following general formula (2): [ka] (In general formula (1), R1 represents a hydrogen atom or a methyl group, and R2 represents a hydrocarbon group having an alicyclic structure and having 6 to 12 carbon atoms.) [ka] (In the general formula (2), R3 represents a hydrogen atom or a methyl group, and R4 represents a linear or branched hydrocarbon group having 8 to 18 carbon atoms.) [2] The toner base particles contain a colorant. The toner for developing electrostatic images according to [1]. [3] The polymer has a structural unit different from both the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2), The toner for developing electrostatic images according to [1] or [2]. [4] The other structural units have a structural unit derived from a polymerizable monomer selected from the group consisting of styrene, (meth)acrylic acid, and (meth)acrylic acid esters. The toner for developing electrostatic images according to [3]. [5] The other structural unit has a structural unit derived from (meth)acrylic acid. The toner for developing electrostatic images according to [3] or [4].

[0011] In order to achieve the above object, another aspect of the present invention relates to the following methods for producing a toner for developing electrostatic images [6] to [8]. [6] A step of copolymerizing a polymerizable monomer represented by the following general formula (3) and a polymerizable monomer represented by the following general formula (4) to obtain a polymer; forming toner particles comprising the resulting polymer; having A method for producing a toner for developing electrostatic images. [ka] (In general formula (3), R1 represents a hydrogen atom or a methyl group, and R2 represents a hydrocarbon group having an alicyclic structure and having 6 to 12 carbon atoms.) [ka] (In the general formula (4), R3 represents a hydrogen atom or a methyl group, and R4 represents a linear or branched hydrocarbon group having 8 to 18 carbon atoms.) [7] In the step of forming toner particles, toner particles containing the polymer and a colorant are formed. A method for producing the toner for developing electrostatic images according to [6]. [8] The step of obtaining the polymer is a step of obtaining a dispersion of the polymer, the step of forming the toner particles is a step of mixing a dispersion of the polymer; The method for producing the toner for developing electrostatic images according to [6] or [7].

[0012] In order to achieve the above object, another aspect of the present invention relates to an image forming method as described below in [9]. [9] A step of adhering the toner for developing electrostatic images according to any one of [1] to [5] to a recording medium; a step of fixing the electrostatic image developing toner adhered to the recording medium; The image forming method according to claim 1,

[0013] In order to achieve the above object, another aspect of the present invention relates to an image forming apparatus as set forth below in

[10] .

[10] An attachment section that attaches the toner for developing electrostatic images according to any one of [1] to [5] to a recording medium; a fixing section for fixing the electrostatic image developing toner adhered to the recording medium; An image forming apparatus comprising: Effect of the Invention

[0014] According to the present invention, there are provided a toner for developing electrostatic images, which is capable of forming images that are less susceptible to sticking caused by charging due to contact with each component of the image forming apparatus, and which has high low-temperature fixing properties and is less susceptible to hot offset, an image forming method using the toner for developing electrostatic images, and an image forming apparatus for forming images using the toner for developing electrostatic images. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a schematic diagram showing an example of an image forming apparatus. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] 1. Toner for developing electrostatic images One embodiment of the present invention relates to a toner for developing an electrostatic image (hereinafter, simply referred to as "toner") for developing an electrostatic image (electrostatic latent image) formed on an image carrier such as a photoconductor. The toner may be a one-component developer made of toner base particles, or a two-component developer having toner base particles and carrier particles.

[0017] 1-1. Toner base particles The toner base particles have a binder resin for fixing the toner to a recording medium. The toner base particles may contain a colorant and other components inside the particles. The toner may be a colored toner in which the toner base particles contain a colorant, or a clear toner in which the toner base particles do not contain a colorant. The toner base particles may also contain an external additive added as a post-treatment agent on the surface thereof.

[0018] 1-1-1. Binder resin The binder resin binds the toner to the recording medium and is preferably a thermoplastic resin.

[0019] (acrylic polymer) In this embodiment, the binder resin contains a polymer (hereinafter also simply referred to as "acrylic polymer") having a constitutional unit represented by the following general formula (1) and a constitutional unit represented by the following general formula (2).

[0020] [ka]

[0021] In general formula (1), R1 represents a hydrogen atom or a methyl group, and R2 represents a hydrocarbon group having an alicyclic structure and having 6 to 12 carbon atoms.

[0022] [ka]

[0023] In general formula (2), R3 represents a hydrogen atom or a methyl group, and R4 represents a linear or branched hydrocarbon group having 8 to 18 carbon atoms.

[0024] In this specification, (meth)acrylic means acrylic or methacrylic, (meth)acrylonitrile means acrylonitrile or methacrylonitrile, and (meth)acrylate means acrylate and methacrylate, respectively.

[0025] According to the findings of the present inventors, polymers having an alicyclic structure have a high dielectric tangent (tan δ) and tend to leak electric charges. Therefore, the structural unit having an alicyclic structure represented by the general formula (1) can prevent the image from sticking to other recording media due to charging. On the other hand, the bulky alicyclic structure causes three-dimensional repulsion of the polymer molecules, reduces the entanglement of the molecular chains, and reduces the elastic properties of the binder resin. Therefore, toners containing polymers having an alicyclic structure are prone to hot offset due to reduced elastic properties. In addition, structural units having an alicyclic structure improve the glass transition temperature (Tg) of the polymer. Therefore, toners containing polymers having an alicyclic structure are prone to low-temperature fixability.

[0026] In contrast, the acrylic polymer used in this embodiment has high crystallinity due to the long-chain hydrocarbon group in the side chain of the structural unit represented by general formula (2), and therefore the toner has high low-temperature fixability.

[0027] In addition, a polymer having a long-chain hydrocarbon group in a side chain can improve the low-temperature fixability of a toner because the long-chain hydrocarbon groups are oriented to each other to form a crystal with a folded structure. On the other hand, the long-chain hydrocarbon group reduces the polarity of the polymer and reduces the molecular motion of the polymer due to its high crystallization ability, thereby reducing the dielectric tangent (tan δ) of the polymer. Therefore, a toner containing a polymer having a long-chain hydrocarbon group is less likely to leak charge and is more likely to stick to other recording media due to the charging of the image. In addition, a polymer with high crystallinity is less likely to cause molecular motion, which tends to reduce the elasticity of the binder resin. Therefore, a toner containing a polymer having a long-chain hydrocarbon group is more likely to cause hot offset due to reduced elasticity.

[0028] In contrast, in the acrylic polymer, the constituent unit represented by general formula (1) partially restricts the crystallization of the hydrocarbon group by virtue of its bulky alicyclic structure. As a result, the acrylic polymer in the toner fixed on a recording medium has partially crystallized and partially uncrystallized portions. Therefore, the acrylic polymer has a high dielectric tangent (tan δ) despite having a long-chain hydrocarbon group in its side chain. This allows the acrylic polymer to easily leak charge from the binder resin, making it less likely for the image to stick to other recording media due to charging.

[0029] In addition, in the acrylic polymer, the main chains of the acrylic polymer are entangled in the non-crystallized portions. Furthermore, in the non-crystallized portions, the long-chain hydrocarbon groups in the side chains of the structural units represented by general formula (2) are entangled with each other. Due to this entanglement of molecular chains and side chains, the acrylic polymer can increase the elastic properties of the binder resin and make hot offset less likely to occur.

[0030] In addition, when the toner is a color toner containing a pigment or dye, if the elasticity of the binder resin is reduced due to the constituent unit having an alicyclic structure, the toner is likely to flow into the gaps between the fibers of the recording medium (paper), and the white part of the paper is likely to be exposed, which tends to cause unevenness in image density. In contrast, the acrylic polymer used in this embodiment increases the elasticity of the binder resin by the above-mentioned action, and therefore can make it difficult for unevenness in image density to occur, despite having an alicyclic structure or a long-chain hydrocarbon group in the side chain.

[0031] In general formula (1), R1 represents a hydrogen atom or a methyl group. From the viewpoint of effectively partially restricting the crystallization of the above-mentioned hydrocarbon group and making it more difficult for an image to stick to other recording media, it is preferable that the structural unit represented by general formula (1) contains a structural unit in which R1 is a methyl group.

[0032] R2 in the general formula (1) represents a hydrocarbon group having an alicyclic structure with 6 to 12 carbon atoms. By setting the carbon number of R2 within the above range, it is possible to effectively suppress hot offset, sticking, and image density unevenness by partially restricting crystallization. In addition, by setting the carbon number of R2 within the above range, it is also possible to suppress the deterioration of low-temperature fixability of the toner due to the alicyclic structure. Examples of the hydrocarbon group having an alicyclic structure include an isobornyl group, an adamantyl group, a cyclohexyl group, and a dicyclopentanyl group. From the viewpoint of efficiently achieving the effects of improving low-temperature fixability by the above-mentioned action, suppressing sticking to other recording media, suppressing hot offset, and suppressing image density unevenness, it is preferable that R2 has a bulky structure, and specifically, it is preferable that R2 has a plurality of cyclic structures. For example, R2 is preferably an isobornyl group or an adamantyl group, and among these, an isobornyl group is more preferable because the low-temperature fixability is less likely to decrease.

[0033] R3 in general formula (2) represents a hydrogen atom or a methyl group. From the viewpoint of improving the low-temperature fixing property of the toner, it is preferable that the structural unit represented by general formula (2) contains a structural unit in which R3 is a hydrogen atom. On the other hand, from the viewpoint of effectively partially restricting the crystallization of the above-mentioned hydrocarbon group, more effectively suppressing the sticking of the image to other recording media, and making hot offset less likely to occur, it is preferable that the structural unit represented by general formula (2) contains a structural unit in which R3 is a methyl group. From the viewpoint of achieving both of these favorably, it is preferable that the structural unit represented by general formula (2) contains both a structural unit in which R3 is a methyl group and a structural unit in which R3 is a hydrogen atom.

[0034] When a structural unit in which R3 is a hydrogen atom and a structural unit in which R3 is a methyl group are used in combination, it is preferable that in the structural unit in which R3 is a methyl group, R4 is a linear alkyl group having from 8 to 12 carbon atoms. From the viewpoint of improving low-temperature fixability, the proportion of structural units in which R3 is a methyl group is preferably from 1% by mass to 50% by mass relative to the total mass of structural units in which R3 is a hydrogen atom.

[0035] R4 in general formula (2) represents a linear or branched hydrocarbon group having 8 to 18 carbon atoms. From the viewpoints of increasing the partial crystallization control effect, increasing the elastic properties of the binder resin by entanglement of side chains, more effectively suppressing image sticking, and making hot offset less likely to occur, the number of carbon atoms in R4 is preferably 8 to 12, more preferably 8 to 10, and even more preferably 8. Note that, from the viewpoint of improving low-temperature fixability, the number of carbon atoms in R4 is preferably an even number.

[0036] From the viewpoint of further improving the low-temperature fixing property of the toner and further increasing the elasticity of the binder resin by entanglement of the side chains, thereby making hot offset less likely to occur and making image density unevenness less likely to occur, it is preferable that the structural unit represented by general formula (2) contains a structural unit in which R4 is a straight-chain hydrocarbon group. On the other hand, from the viewpoint of effectively partially restricting crystallization and making it less likely that the image will stick to other recording media, it is preferable that the structural unit represented by general formula (2) contains a structural unit in which R4 is a branched-chain hydrocarbon group.

[0037] The acrylic polymer may have other structural units different from both the structural units represented by general formula (1) and the structural units represented by general formula (2). Examples of the other structural units include structural units derived from styrene and its derivatives, monomers having a carboxyl group such as (meth)acrylic acid, maleic acid, itaconic acid, and fumaric acid, and (meth)acrylic acid esters. These structural units can increase the elastic properties of the binder resin by entanglement of the side chains, making it more difficult for hot offset to occur and more difficult for image density unevenness to occur. Among these, from the viewpoint of making it easier to control the particle size of the toner base particles and suppressing the occurrence of image density unevenness due to large particle size, structural units having a carboxyl group are preferred, and structural units derived from (meth)acrylic acid are more preferred. Furthermore, from the viewpoint of further increasing the elastic properties, making it more difficult for hot offset to occur and more difficult for image density unevenness to occur, structural units derived from methacrylic acid are more preferred.

[0038] Examples of the (meth)acrylic acid ester include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, stearyl (meth)acrylate, lauryl (meth)acrylate, phenyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and diethylaminoethyl (meth)acrylate.

[0039] The mass ratio of the structural unit represented by formula (1) to the total mass of the acrylic polymer is preferably 10% by mass or more and 80% by mass or less, and more preferably 20% by mass or more and 70% by mass or less. The higher the mass ratio of the structural unit represented by formula (1), the more unlikely it is that the image will stick to other recording media.

[0040] The mass ratio of the structural unit represented by general formula (2) to the total mass of the acrylic polymer is preferably 5% by mass or more and 75% by mass or less, more preferably 10% by mass or more and 70% by mass or less, and even more preferably 20% by mass or more and 60% by mass or less. The higher the mass ratio of the structural unit represented by general formula (2), the higher the low-temperature fixability of the toner. It is also possible to adjust the resistance to hot offset and image density unevenness by adjusting the mass ratio of the structural unit represented by general formula (1) and the mass ratio of the structural unit represented by general formula (2).

[0041] Furthermore, in the acrylic polymer, the mass proportion of other structural units relative to the total mass is preferably from 1 mass % to 80 mass %, and more preferably from 2 mass % to 70 mass %.

[0042] The acrylic polymer preferably has a peak molecular weight in the molecular weight distribution measured using a refractive index detector (RI detector) of 3,500 or more and 35,000 or less, and more preferably 10,000 or more and 30,000 or less. When the peak molecular weight is within the above range, the melt viscosity of the acrylic polymer during fixing tends to be in an appropriate range, and it is easy to achieve both the fixing property and offset resistance of the toner.

[0043] The "peak molecular weight" means a molecular weight corresponding to the elution time of the peak top in the molecular weight distribution. When multiple peaks exist in the molecular weight distribution, the molecular weight corresponding to the elution time of the peak top with the largest peak area ratio is defined as the peak molecular weight.

[0044] The content of the acrylic polymer is preferably 65 parts by mass or more and 98 parts by mass or less, more preferably 70 parts by mass or more and 95 parts by mass or less, and even more preferably 75 parts by mass or more and 93 parts by mass or less, relative to 100 parts by mass of the total amount of the binder resin.

[0045] (Other binder resins) The binder resin may contain other resins in addition to the acrylic polymers. Examples of the other resins include thermoplastic resins such as styrene resins, vinyl resins (such as (meth)acrylic resins and styrene-(meth)acrylic resins), polyester resins, silicone resins, olefin resins, polyamide resins, and epoxy resins.

[0046] The other resin may be an amorphous resin, a crystalline resin, or a composite resin in which a crystalline resin and an amorphous resin are hybridized.

[0047] In this specification, the term "crystalline resin" refers to a resin whose melting point is observed in a measurement by differential scanning calorimetry (DSC). In addition, the term "amorphous resin" refers to a resin whose melting point is not observed in a measurement by DSC. In addition, in this specification, "a resin whose melting point is observed" refers to a peak whose half-width of the endothermic peak is within 15°C when measured by DSC at a heating rate of 10°C / min.

[0048] Examples of other resins include styrene-based polymers (styrene homopolymers, homopolymers of styrene substitutes such as poly-p-chlorostyrene and polyvinyltoluene, and styrene-based copolymers such as styrene-p-chlorostyrene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-butadiene copolymers, and styrene-isoprene copolymers), polyvinyl chloride, phenolic resins, vinyl resins such as (meth)acrylic resins (including styrene-(meth)acrylic acid ester copolymers, styrene-α-chloro(meth)acrylic acid methyl copolymers, styrene-(meth)acrylonitrile copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl ethyl ether copolymers, styrene-vinyl methyl ketone copolymers, and styrene-acrylonitrile-indene copolymers), polyvinyl acetate, silicone resins, polyester resins, polyurethane resins, polyamide resins, furan resins, epoxy resins, xylene resins, polyvinyl butyral, terpene resins, coumarone-indene resins, natural resins, modified natural resins (naturally modified phenolic resins and natural resin modified maleic acid resins), and other petroleum-based resins. Of these, vinyl resins and polyester resins are preferred because they have a polarity close to that of varnish and are therefore likely to improve the adhesion of the varnish, and polyester resins are more preferred.

[0049] From the viewpoint of enhancing the low-temperature fixing property of the toner, it is preferable that the binder resin contains a crystalline polyester. The crystalline polyester can also prevent the image from sticking to other recording media due to electrostatic charge.

[0050] The crystalline polyester is usually obtained by subjecting a polyvalent carboxylic acid and a polyhydric alcohol to a dehydration condensation reaction by a known method.

[0051] The polycarboxylic acid may be a divalent or higher carboxylic acid, and may be a trivalent or higher carboxylic acid such as trimellitic acid or pyromellitic acid. Among these, dicarboxylic acids are preferred from the viewpoint of increasing the crystallinity of the crystalline polyester. Examples of dicarboxylic acids include aliphatic carboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,11-undecanedicarboxylic acid, 1,12-dodecanedicarboxylic acid (dodecanedioic acid), 1,13-tridecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,16-hexadecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid, as well as aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, orthophthalic acid, t-butylisophthalic acid, 2,6-naphthalenedicarboxylic acid, and 4,4'-biphenyldicarboxylic acid. The crystalline polyester may contain only one type of structural unit derived from these carboxylic acids, or may contain two or more types of structural units derived from these carboxylic acids.

[0052] Among these, aliphatic carboxylic acids are preferred because they are easy to increase the crystallinity of the crystalline polyester and also easy to increase the affinity between the diol di(meth)acrylate that may be contained in the varnish and the crystalline polyester. The aliphatic carboxylic acids preferably have a linear hydrocarbon group having 6 to 16 carbon atoms, more preferably a linear hydrocarbon group having 10 to 14 carbon atoms. The hydrocarbon structure of the aliphatic carboxylic acid may be partially branched.

[0053] The polyhydric alcohol may be a dihydric or higher alcohol, and may be a trihydric or higher alcohol such as glycerin, pentaerythritol, trimethylolpropane, sorbitol, etc. Among these, dihydric alcohols are preferred from the viewpoint of increasing the crystallinity of the crystalline polyester. Examples of the dihydric alcohol include aliphatic diols such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,20-eicosanediol, diols having an unsaturated double bond such as 2-butene-1,4-diol, 3-hexene-1,6-diol, and 4-octene-1,8-diol, and diols having a sulfonic acid group.

[0054] From the viewpoint of sufficiently softening the toner base particles and enhancing the low-temperature fixability of the toner, the melting point of the crystalline polyester is preferably 50°C or more and 85°C or less, and more preferably 60°C or more and 80°C or less.

[0055] The weight average molecular weight (Mw) of the crystalline polyester is preferably 5000 or more and 50000 or less. The number average molecular weight (Mn) of the crystalline polyester is preferably 2000 or more and 10000 or less. When the weight average molecular weight (Mw) and number average molecular weight (Mn) of the crystalline polyester are within the above ranges, the low temperature fixability is improved.

[0056] In order to fully achieve the above-mentioned effects, the content of the crystalline polyester is preferably 5 parts by mass or more and 20 parts by mass or less, and more preferably 8 parts by mass or more and 15 parts by mass or less, per 100 parts by mass of the total amount of the binder resin.

[0057] The content of the binder resin is preferably 20% by mass or more and 99% by mass or less, more preferably 30% by mass or more and 95% by mass or less, and even more preferably 40% by mass or more and 90% by mass or less, based on the total mass of the toner base particles. When the content of the binder resin is 20% by mass or more, the strength of the formed image can be further increased.

[0058] 1-1-2. Coloring agent The colorant may be a dye or a pigment. When the toner is a color toner that imparts a predetermined color tone to an image, the toner base particles may contain a colorant such as yellow, magenta, cyan, or black, depending on the color tone to be presented by the color toner. The toner base particles may contain only one type of colorant, or may contain a combination of multiple types of colorants.

[0059] Examples of yellow colorants include yellow dyes, including CI Solvent Yellow 19, 44, 77, 79, 81, 82, 93, 98, 103, 104, 112, and 162, and the like; and yellow pigments, including CI Pigment Yellow 14, 17, 74, 93, 94, 138, 155, 180, and 185, and the like.

[0060] Examples of magenta colorants include magenta dyes, including CI Solvent Red 1, 49, 52, 58, 63, 111, and 122, and the like; and magenta pigments, such as CI Pigment Red 5, 48:1, 53:1, 57:1, 122, 139, 144, 149, 166, 177, 178, and 222.

[0061] Examples of cyan colorants include cyan dyes, such as CI Solvent Blue 25, 36, 60, 70, 93, and 95, and cyan pigments, such as CI Pigment Blue 1, 7, 15, 15:3, 60, 62, 66, and 76.

[0062] Examples of black colorants include carbon blacks, including channel black, furnace black, acetylene black, thermal black, and lamp black; magnetic materials, including ferrite and magnetite; and iron-titanium composite oxides.

[0063] The content of the colorant is preferably 0.5% by mass or more and 20% by mass or less, more preferably 2% by mass or more and 10% by mass or less, based on the total mass of the toner base particles. When the toner is a clear toner, it is preferable that the toner base particles do not substantially contain a colorant, and the content of the colorant is preferably 0.1% by mass or less based on the total mass of the toner base particles.

[0064] 1-1-3.Other ingredients The toner base particles may contain other ingredients, such as release agents and charge control agents.

[0065] The release agent enhances the releasability of the toner from the fixing member, etc. The release agent is preferably a wax.

[0066] Examples of the release agent that is a wax include hydrocarbon waxes including polyethylene wax, paraffin wax, microcrystalline wax, and Fischer-Tropsch wax, dialkyl ketone waxes including distearyl ketone, carnauba wax, montan wax, ester waxes including behenic acid behenate, trimethylolpropane tribehenate, pentaerythritol tetramyristate, pentaerythritol tetrastearate, pentaerythritol tetrabehenate, pentaerythritol diacetate dibehenate, glycerin tribehenate, 1,18-octadecanediol distearate, trimellitic acid tristearyl, and distearyl maleate, and amide waxes including ethylenediamine dibehenylamide, and trimellitic acid tristearylamide.

[0067] The hydrocarbon wax preferably has a melting point of 50° C. or higher and 95° C. or lower. When the melting point of the hydrocarbon wax is 50° C. or higher, the hydrocarbon wax exuded from the toner particles is easily crystallized, and the release effect and the abrasion resistance of the formed image are easily improved. When the melting point of the hydrocarbon wax is 95° C. or lower, the hydrocarbon wax is easily exuded from the toner base particles during fixing, and the release effect and the abrasion resistance of the formed image are easily improved. In addition, when the melting point of the hydrocarbon wax is 95° C. or lower, the toner base particles are easily melted during fixing, and the low-temperature fixability of the toner is easily improved.

[0068] The content of the release agent is preferably 3% by mass or more and 20% by mass or less, more preferably 5% by mass or more and 15% by mass or less, based on the total mass of the toner base particles. When the content of the release agent is 3% by mass or more, the releasability of the toner from the fixing member is sufficiently improved. When the content of the release agent is 20% by mass or less, a sufficient amount of the binder resin can be contained in the toner base particles, so that the fixability of the image is sufficiently improved.

[0069] The charge control agent adjusts the chargeability of the toner base particles.

[0070] Examples of the charge control agent include nigrosine dyes, metal salts of naphthenic acid or higher fatty acids, alkoxylated amines, quaternary ammonium salt compounds, azo metal complexes, metal salicylates or metal complexes thereof, and the like.

[0071] The content of the charge control agent is preferably 0.1% by mass to 10% by mass, more preferably 0.5% by mass to 5% by mass, based on the total mass of the binder resin. If an attempt is made to control the chargeability of the toner by adding an excessive amount of the charge control agent, other properties of the toner base particles may change significantly. In contrast, in this embodiment, the chargeability of the toner is adjusted by strontium titanate, so that the chargeability of the toner can be adjusted to a desired level while satisfying other required properties.

[0072] 1-1-4.External additives The toner base particles may contain an external additive that is added to the surface of the toner base particles as a post-treatment agent in order to enhance the fluidity, chargeability and cleanability of the toner.

[0073] Examples of the external additive include strontium titanate particles, silica particles, alumina particles, zirconia particles, zinc oxide particles, chromium oxide particles, cerium oxide particles, antimony oxide particles, tungsten oxide particles, tin oxide particles, tellurium oxide particles, manganese oxide particles, and boron oxide particles. If necessary, these particles may be hydrophobized with a surface treatment agent such as a silane coupling agent or silicone oil. The particle size of these particles is preferably 20 nm or more and 200 nm or less, more preferably 30 nm or more and 150 nm or less, in terms of the number average primary particle size measured by the same method as that of strontium titanate.

[0074] The number-average primary particle diameter of the external additive can be determined by binarizing image data of the external additive taken with a scanning electron microscope (SEM) using an image processing analyzer (LUZEX AP, manufactured by Nireco Corporation) and averaging the horizontal Feret diameters measured for 100 particles.

[0075] The external additive may contain particles mainly composed of an organic material including homopolymers such as styrene and methyl methacrylate, or copolymers thereof, etc. The particle size of these particles is preferably 10 nm or more and 1000 nm or less in terms of the peak top particle size measured by the same method as for strontium titanate.

[0076] The external additive may also contain a lubricant such as a metal salt of a higher fatty acid. The higher fatty acid salts include stearic acid, oleic acid, palmitic acid, linoleic acid, and ricinoleic acid. Examples of metals constituting the metal salts include zinc, manganese, aluminum, iron, copper, magnesium, and calcium.

[0077] The content of these external additives is preferably 0.05% by mass or more and 5.0% by mass or less based on the total mass of the toner base particles.

[0078] 1-3. Characteristics of toner base particles The toner base particles preferably have a volume-based average particle size of 3.0 μm or more and 10.0 μm or less, more preferably 5.0 μm or more and 8.0 μm or less, and even more preferably 5.5 μm or more and 7.0 μm or less.

[0079] The volume-based average particle size of the toner base particles can be measured using a measuring device that is a particle size distribution measuring device (Coulter Multisizer 3, manufactured by Beckman Coulter, Inc.) connected to a computer system equipped with data processing software Software V3.51. Specifically, 0.02 g of a sample (toner base particles) is added to 20 mL of a surfactant solution (a surfactant solution obtained by diluting, for example, a neutral detergent containing a surfactant component 10 times with pure water in order to disperse the toner base particles), and then ultrasonic dispersion treatment is performed for 1 minute to prepare a dispersion of the toner base particles. This dispersion is injected with a pipette into a beaker containing an electrolyte (ISOTON II, manufactured by Beckman Coulter, Inc.) in a sample stand until the concentration displayed on the measuring device is 8%. By adjusting the concentration to this level, reproducible measurement values ​​can be obtained. In the measurement device, the number of measured particles is set to 25,000, the aperture diameter is set to 100 μm, the measurement range of 2 to 60 μm is divided into 256 parts to calculate the frequency value, and the volume-based average particle diameter is calculated based on this.

[0080] 1-4. Manufacturing method of toner base particles The toner base particles can be produced in the same manner as known toners, by a pulverization method, an emulsion polymerization aggregation method, an emulsion aggregation method, a suspension polymerization method, a dissolution suspension method or the like.

[0081] Among these, the pulverization method, the emulsion polymerization flocculation method, the emulsion flocculation method, and the suspension polymerization method are preferred, the pulverization method, the emulsion polymerization flocculation method, and the emulsion flocculation method are more preferred, and the emulsion polymerization flocculation method and the emulsion flocculation method are further preferred.

[0082] According to the pulverization method, a binder resin, a release agent, a C16-35 saturated compound, and other materials are mixed and melt-kneaded to obtain a solid resin composition, which is then pulverized to a specified particle size to obtain toner base particles.

[0083] According to the emulsion polymerization flocculation method, a dispersion of binder resin particles obtained by the emulsion polymerization method and a dispersion of pigment particles are mixed together with particles of a release agent and a charge control agent, which are optionally added, and these are aggregated, associated or fused together until particles having a desired particle size are obtained, and then an external additive is added, thereby obtaining the toner.

[0084] According to the emulsion aggregation method, a dispersion of binder resin particles obtained by dropping a solution in which a binder resin is dissolved into a poor solvent is mixed with a dispersion of pigment particles together with particles of a release agent and a charge control agent, which are optionally added, and these are aggregated, associated or fused together until particles of a desired particle size are obtained, and then an external additive is added to obtain the toner.

[0085] Specifically, first, a polymerizable monomer represented by the following general formula (3) and a polymerizable monomer represented by the following general formula (4) are copolymerized to obtain the acrylic polymer.

[0086] [ka]

[0087] In the general formula (3), R1 represents a hydrogen atom or a methyl group, and R2 represents a hydrocarbon group having an alicyclic structure and having 6 to 12 carbon atoms.

[0088] [ka]

[0089] In general formula (4), R3 represents a hydrogen atom or a methyl group, and R4 represents a linear or branched hydrocarbon group having 8 to 18 carbon atoms.

[0090] At this time, polymerizable monomers that are the materials of the above-mentioned other structural units may be copolymerized. The specific types and amounts of these polymer monomers may be set according to the types and amounts of each structural unit contained in the above-mentioned acrylic polymer. At this time, a mercapto compound such as n-octyl-3-mercaptopropionate may be used in combination as a chain transfer agent.

[0091] The acrylic polymer thus obtained may be used to form toner base particles containing the acrylic polymer by the above-mentioned methods. For example, in the emulsion polymerization aggregation method or emulsion aggregation method, a dispersion of the acrylic polymer may be mixed with a dispersion of a crystalline polyester, a dispersion of a colorant (or a dispersion of resin particles containing a colorant), or a dispersion of a release agent (or a dispersion of resin particles containing a release agent), and these particles may be aggregated.

[0092] The toner base particles obtained through the above steps may be used as is, but may be externally treated with an external additive if necessary. The external addition treatment with an external additive can be performed by mixing a predetermined amount of the toner base particles and the external additive, and stirring and mixing them with a mixing device such as a double con mixer, a V-type mixer, a drum type mixer, a super mixer, a Henschel mixer, a Nauta mixer, a Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.), or a Nobilta (manufactured by Hosokawa Micron Corporation).

[0093] 1-2.Career The carrier is mixed with the above-mentioned toner base particles to form a two-component magnetic toner. The carrier may be any known magnetic particle that can be contained in a toner.

[0094] Examples of the magnetic particles include particles containing magnetic materials such as iron, steel, nickel, cobalt, ferrite, and magnetite, as well as alloys of these with aluminum and lead. The carrier may be a coated carrier in which the surface of a particle made of the magnetic material is coated with a resin or the like, or a resin-dispersed carrier in which the magnetic material is dispersed in a binder resin. Examples of the resin for coating include olefin resin, styrene resin, styrene-acrylic resin, silicone resin, polyester resin, and fluororesin. Examples of the binder resin include acrylic resin, styrene-acrylic resin, polyester resin, fluororesin, and phenol resin.

[0095] The average particle size of the carrier is preferably 20 μm or more and 100 μm or less, more preferably 25 μm or more and 80 μm or less, on a volume basis. The average particle size of the carrier can be measured by a laser diffraction type particle size distribution measuring device equipped with a wet disperser, such as HELOS manufactured by SYMPATEC.

[0096] The content of the carrier is preferably 2% by mass or more and 10% by mass or less with respect to the total mass of the toner base particles and the carrier.

[0097] 2. Image forming method and image forming apparatus Another embodiment of the present invention relates to an image forming apparatus including a toner image forming section that develops an electrostatic latent image with a toner to form a toner image, and a fixing device that transfers the toner image to a recording medium and fixes the toner image to the recording medium, and an image forming method using the image forming apparatus. In this embodiment, the fixing device fixes the toner to the recording medium.

[0098] The image forming apparatus may be a four-cycle type image forming apparatus consisting of four types of color developing devices, namely, yellow, magenta, cyan, and black, and one electrophotographic photosensitive member, or may be a tandem type image forming apparatus consisting of four types of color developing devices, namely, yellow, magenta, cyan, and black, and four electrophotographic photosensitive members, one for each color.

[0099] 3 is a schematic diagram showing an example of an image forming apparatus 1 according to the present embodiment. The image forming apparatus 1 shown in FIG. 3 includes an image processing section 30, an image forming section 40, a paper conveying section 50, a fixing device 60, and an image reading section 70.

[0100] Image forming section 40 has image forming units 41Y, 41M, 41C, and 41K that form images using toners of the respective colors Y (yellow), M (magenta), C (cyan), and K (black). Since these have the same configuration except for the toners contained therein, hereinafter, the symbols representing the colors may be omitted. Image forming section 40 further has an intermediate transfer unit 42 and a secondary transfer unit 43. These correspond to transfer devices.

[0101] The image forming unit 41 includes an exposure device 411, a development device 412, an electrophotographic photoconductor (image carrier) 413, a charging device 414, and a drum cleaning device 415. The charging device 414 is, for example, a corona charger. The charging device 414 may be a contact charging device that charges the electrophotographic photoconductor 413 by contacting a contact charging member such as a charging roller, a charging brush, or a charging blade with the electrophotographic photoconductor 413. The exposure device 411 includes, for example, a semiconductor laser as a light source, and a light deflection device (polygon motor) that irradiates the electrophotographic photoconductor 413 with laser light according to an image to be formed. The electrophotographic photoconductor 413 is a negatively charged organic photoconductor having photoconductivity. The electrophotographic photoconductor 413 is charged by the charging device 414.

[0102] The developing device 412 is a two-component developing device. The developing device 412 has, for example, a developing container that contains a two-component developer, a developing roller (magnetic roller) that is rotatably arranged at the opening of the developing container, a partition that divides the inside of the developing container so that the two-component developer can communicate with each other, a transport roller for transporting the two-component developer on the opening side of the developing container toward the developing roller, and a stirring roller for stirring the two-component developer in the developing container. The developing container contains, for example, a two-component developer.

[0103] Intermediate transfer unit 42 has intermediate transfer belt (intermediate transfer body) 421, primary transfer roller 422 that presses intermediate transfer belt 421 against electrophotographic photosensitive body 413, multiple support rollers 423 including backup roller 423A, and belt cleaning device 426. Intermediate transfer belt 421 is stretched in a loop shape around multiple support rollers 423. Intermediate transfer belt 421 runs at a constant speed in the direction of arrow A as at least one drive roller among multiple support rollers 423 rotates.

[0104] The belt cleaning device 426 has an elastic member 426a. The elastic member 426a comes into contact with the intermediate transfer belt 421 after the secondary transfer, and removes deposits on the surface of the intermediate transfer belt 421. The elastic member 426a is made of an elastic body, and includes a cleaning blade, a brush, and the like.

[0105] The secondary transfer unit 43 has an endless secondary transfer belt 432 and a plurality of support rollers 431 including a secondary transfer roller 431A. The secondary transfer belt 432 is stretched by the secondary transfer roller 431A and the support rollers 431 in a loop shape.

[0106] The fixing device 60 has, for example, a fixing roller 62, an endless heating belt 10 that covers the outer peripheral surface of the fixing roller 62 and heats and melts the toner that constitutes the toner image on the paper S, and a pressure roller 63 that presses the paper S against the fixing roller 62 and the heating belt 10. The paper S corresponds to a recording medium.

[0107] Image forming apparatus 1 further includes an image reading section 70, an image processing section 30, and a paper transport section 50. Image reading section 70 includes a paper feeder 71 and a scanner 72. Paper transport section 50 includes a paper feed section 51, a paper discharge section 52, and a transport path section 53. Three paper feed tray units 51a to 51c that make up paper feed section 51 store paper S (standard paper, special paper) identified based on basis weight, size, etc., by preset type. Transport path section 53 includes a plurality of transport roller pairs, such as registration roller pair 53a.

[0108] The formation of an image by the image forming apparatus 1 will be described. The scanner 72 optically scans and reads the document D on the contact glass. The reflected light from the document D is read by the CCD sensor 72a and becomes input image data. The input image data is subjected to predetermined image processing in the image processing unit 30 and sent to the exposure device 411.

[0109] Electrophotographic photoreceptor 413 rotates at a constant peripheral speed. Charging device 414 uniformly charges the surface of electrophotographic photoreceptor 413 to negative polarity. In exposure device 411, a polygon mirror of a polygon motor rotates at high speed, and laser light corresponding to input image data of each color component is developed along the axial direction of electrophotographic photoreceptor 413 and irradiated onto the outer circumferential surface of electrophotographic photoreceptor 413 along the axial direction. In this way, an electrostatic latent image is formed on the surface of electrophotographic photoreceptor 413.

[0110] In the developing device 412, the toner base particles are charged by stirring and transporting the two-component developer in the developing container, and the two-component developer is transported to the developing roller, which forms a magnetic brush on the surface of the developing roller. The charged toner base particles electrostatically adhere from the magnetic brush to the electrostatic latent image on the electrophotographic photoreceptor 413. In this way, the electrostatic latent image on the surface of the electrophotographic photoreceptor 413 is visualized, and a toner image corresponding to the electrostatic latent image is formed on the surface of the electrophotographic photoreceptor 413. The term "toner image" refers to the state in which toner is gathered in the form of an image.

[0111] The toner image on the surface of the electrophotographic photoreceptor 413 is transferred to an intermediate transfer belt 421 by an intermediate transfer unit 42. Residual toner remaining on the surface of the electrophotographic photoreceptor 413 after the transfer is removed by a drum cleaning device 415 having a drum cleaning blade that is in sliding contact with the surface of the electrophotographic photoreceptor 413.

[0112] The intermediate transfer belt 421 is pressed against the electrophotographic photoreceptor 413 by the primary transfer roller 422, whereby a primary transfer nip is formed for each electrophotographic photoreceptor by the electrophotographic photoreceptor 413 and the intermediate transfer belt 421. In the primary transfer nip, toner images of each color are transferred to the intermediate transfer belt 421 in order, superimposed thereon.

[0113] Meanwhile, secondary transfer roller 431A is pressed against backup roller 423A via intermediate transfer belt 421 and secondary transfer belt 432. As a result, a secondary transfer nip is formed by intermediate transfer belt 421 and secondary transfer belt 432. Paper S passes through the secondary transfer nip. Paper S is transported to the secondary transfer nip (attachment portion) by paper transport section 50. Correction of the inclination of paper S and adjustment of the transport timing are performed by a registration roller section in which registration roller pair 53a is arranged.

[0114] When the paper S is transported to the secondary transfer nip, a transfer bias is applied to the secondary transfer roller 431A. By applying this transfer bias, the toner image carried on the intermediate transfer belt 421 is transferred to the paper S (a process of adhering the toner for developing an electrostatic image to a recording medium). The paper S to which the toner image has been transferred is transported toward the fixing device 60 by the secondary transfer belt 432.

[0115] Any deposits such as residual toner remaining on the surface of intermediate transfer belt 421 after the secondary transfer are removed by a belt cleaning device 426 having a cleaning blade that is in sliding contact with the surface of intermediate transfer belt 421. At this time, since the above-mentioned intermediate transfer body is used as the intermediate transfer belt, it is possible to reduce dynamic frictional force over time.

[0116] The fixing device 60 sandwiches the heating belt 10 between a rotating fixing roller 62 and a pressure roller 63 to form a fixing nip, and heats and presses the conveyed paper S in the fixing nip. In this way, the toner image is fixed to the paper S (a process of fixing the toner for developing an electrostatic image to a recording medium). The paper S with the fixed toner image is discharged outside the machine by a paper discharge section 52 equipped with a paper discharge roller 52a.

[0117] The above-described apparatus configuration and image forming method are merely illustrative embodiments for carrying out the present invention, and the present invention is not limited to these. EXAMPLES

[0118] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these.

[0119] In the following examples, unless otherwise specified, the average particle size of each particle is the volume-based average particle size measured using a Coulter Multisizer 3 manufactured by Beckman Coulter.

[0120] 1. Manufacture of toner for developing electrostatic images 1-1. Preparation of Toner 1 1-1-1. Preparation of acrylic polymer particle dispersion A surfactant solution prepared by dissolving 8 g of sodium dodecyl sulfate in 3 L of ion-exchanged water was placed in a 5 L stainless steel pot (SUS pot) equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen introducing device, and the liquid temperature was raised to 80°C while stirring at a stirring speed of 230 rpm under a nitrogen stream.

[0121] To this surfactant solution, an initiator solution prepared by dissolving 10 g of potassium persulfate in 200 g of ion-exchanged water was added. After the addition, the temperature was adjusted to 80° C., and a monomer mixture having the following composition was added dropwise over a period of 100 minutes. -Monomer mixture- A polymerizable monomer represented by the general formula (3): Isobornyl acrylate (IBXA) 568g A polymerizable monomer represented by the general formula (4): n-Octyl acrylate (OA) 184g Other monomers: Methacrylic acid (MAA) 48g Polymerization initiator: n-Octyl-3-mercaptopropionate 5.5g

[0122] The system to which the monomer mixture was added dropwise was heated and stirred for 2 hours while keeping the temperature at 80° C. to react the polymerizable monomers and prepare a dispersion of acrylic polymer particles.

[0123] The volume-based median diameter (d50) of the acrylic polymer particles contained in the obtained dispersion of acrylic polymer particles was measured by dynamic light scattering using "Microtrac UPA-150" (manufactured by Nikkiso Co., Ltd.) and was found to be 115 nm.

[0124] The peak molecular weight of the acrylic polymer was measured by the following method and was found to be 21,100.

[0125] The apparatus "HLC-8220" (manufactured by Tosoh Corporation) and the column "TSK guard column + TSK gel Super HZM-M triplet" (manufactured by Tosoh Corporation) were used. While the column temperature was kept at 40°C, tetrahydrofuran (THF) was passed as a carrier solvent at a flow rate of 0.2 ml / min, and the solvent temperature was set to room temperature (25°C), and ultrasonic treatment was performed for 5 minutes using an ultrasonic disperser. As a result, a tetrahydrofuran solution of an acrylic polymer with a concentration of 1 mg / ml was obtained.

[0126] This solution was treated with a membrane filter with a pore size of 0.2 μm to obtain a sample solution. 10 μl of the sample solution was injected into the device together with the carrier solvent, and the molecular weight distribution of the acrylic polymer was measured using a refractive index detector (RI detector). The peak molecular weight in the measured molecular weight distribution was determined.

[0127] 1-1-2. Preparation of colorant particle dispersion The following materials were prepared: Colorant: 10 parts by weight Surfactant: 1.5 parts by weight Ion-exchanged water: 90 parts by weight

[0128] Carbon black (Mogul (registered trademark), manufactured by L. Cabot Corporation) was used as the colorant. A 20% by mass aqueous solution of sodium dodecylbenzenesulfonate was used as the surfactant.

[0129] The above materials were mixed and dispersed using an SC mill to obtain colorant particle dispersion 1. The volume-based median diameter (d50) of the colorant particles contained in the obtained colorant particle dispersion was measured by dynamic light scattering using "Microtrac UPA-150" (manufactured by Nikkiso Co., Ltd.) and found to be 155 nm.

[0130] 1-1-3. Preparation of dispersion of release agent particles The following materials were prepared: Release agent (behenyl behenate): 100 parts by weight Surfactant (sodium dodecyl sulfate): 5 parts by weight Ion-exchanged water: 240 parts by weight

[0131] The above materials were dispersed in a round stainless steel flask by a homogenizer "Ultra Turrax (registered trademark) T50" (manufactured by IKA Co., Ltd.) for 10 minutes, and then further dispersed by a pressure discharge homogenizer to obtain a dispersion of release agent particles. The volume-based median diameter (d50) of the release agent particles in the obtained dispersion of the release agent was measured by a laser diffraction type particle size distribution analyzer LA-750 (manufactured by Horiba, Ltd.) and was found to be 530 nm.

[0132] 1-1-4. Preparation of dispersion of crystalline polyester resin particles 281 parts by mass of dodecanedioic acid and 107 parts by mass of 1,4-butanediol were put into a reaction vessel equipped with a stirrer, a thermometer, a cooling tube, and a nitrogen gas inlet tube. After replacing the inside of the reaction vessel with dry nitrogen gas, 0.1 parts by mass of Ti(On-Bu)4 was added, and the resulting mixture was heated to about 180°C under a nitrogen gas flow and stirred for 8 hours to react the materials. Furthermore, 0.2 parts by mass of Ti(On-Bu)4 was added to the mixture, the temperature of the mixture was raised to about 220°C, and the mixture was stirred for 6 hours, and the reaction was allowed to proceed until the acid value measured in accordance with JIS K0070:1992 reached 20 mgKOH / g. Thereafter, the pressure in the reaction vessel was reduced to 1333.2 Pa, and the reaction was allowed to proceed further under reduced pressure to obtain a crystalline polyester resin. The acid value of the obtained crystalline polyester resin measured in accordance with JIS K0070:1992 was 20 mgKOH / g, the number average molecular weight (Mn) was 5,500, the weight average molecular weight (Mw) was 18,000, and the melting point (Tm) was 72°C.

[0133] 30 parts by mass of the obtained crystalline polyester resin was heated to melt and transferred to an emulsifying and dispersing machine "Cavitron CD1010" (manufactured by Eurotech Co., Ltd.) at a transfer rate of 100 parts by mass per minute. At the same time, 120 parts by mass of dilute ammonia water (concentration 0.37% by mass) was transferred to the emulsifying and dispersing machine at a transfer rate of 0.1 liters per minute while being heated to 100°C by a heat exchanger. The dilute ammonia water was prepared by diluting 70 parts by mass of reagent ammonia water with ion-exchanged water in an aqueous solvent tank.

[0134] Thereafter, the emulsifying and dispersing machine was operated at a rotor speed of 60 Hz and a pressure of 5 kg / cm 2 (490 kPa) to obtain a dispersion of crystalline polyester resin particles with a solid content of 30 parts by mass (solid content concentration: 20% by mass). The volume-based median diameter (d50) of the crystalline polyester resin particles in the obtained dispersion of crystalline polyester resin particles was measured using a Microtrac particle size distribution analyzer "UPA-150" (manufactured by Nikkiso Co., Ltd.) and found to be 200 nm.

[0135] 1-1-5. Preparation of toner base particle dispersion The following materials were prepared: Dispersion of acrylic polymer particles: 237 parts by weight Dispersion of colorant particles: 42 parts by weight Dispersion of release agent particles: 18 parts by weight Polyaluminum chloride: 1.8 parts by weight Ion-exchanged water: 600 parts by weight

[0136] The above materials were mixed and dispersed in a round stainless steel flask using a homogenizer "Ultra Turrax (registered trademark) T50" (manufactured by IKA). The flask was then heated to 55°C while being stirred in a heating oil bath. After the temperature was raised, 60 parts by mass (solid content equivalent) of a dispersion of crystalline polyester resin particles was added to the mixture over 10 minutes to promote particle aggregation. After further holding at 55°C for 30 minutes, it was confirmed that aggregated particles with a volumetric median diameter (D50) of 4.8 μm were generated in the solution. When the temperature of the heating oil bath was further raised and held at 56°C for 2 hours, the volumetric median diameter (D50) became 5.9 μm.

[0137] After that, 1 mol / L of sodium hydroxide was added to the system to adjust the pH of the system to 5.0 at 56°C, and then the round stainless steel flask was sealed with a magnetic seal and heated to 98°C while continuing to stir. Stirring was continued for 6 hours to complete the fusion (fusion) between the binder resin particles, and a dispersion of toner base particles was prepared. The median diameter (D50) of the toner base particles in the dispersion on a volume basis was 6.1 μm.

[0138] The obtained dispersion of the toner base particles was subjected to solid-liquid separation using a basket-type centrifuge "MARK III, model number 60x40" (manufactured by Matsumoto Kikai Hanbai Co., Ltd.) to obtain a wet cake of the toner base particles.

[0139] The obtained wet cake was washed with ion-exchanged water at 45°C using the basket centrifuge until the electrical conductivity of the filtrate reached 5 μS / cm, and then transferred to a "Flash Jet Dryer" (manufactured by Seishin Enterprise Co., Ltd.) and dried until the moisture content was 0.5% by mass, thereby obtaining toner base particles 1.

[0140] 1-1-6. Treatment with external additives To 100 parts by mass of the obtained toner base particles 1, 1 part by mass of hydrophobic silica (number average primary particle diameter: 12 nm) and 0.3 parts by mass of hydrophobic titania (number average primary particle diameter: 20 nm) were added, and the mixture was mixed using a Henschel mixer (registered trademark) for external additive treatment to produce toner 1.

[0141] 1-2. Preparation of Toner 2 to Toner 26 Toners 2 to 26 were obtained in the same manner as in the production of toner 1, except that the type and amount of the polymerizable monomer added when preparing the dispersion liquid of the binder resin particles was changed as shown in Table 1.

[0142] 1-3. Preparation of Toner 27 Toner 27 was obtained in the same manner as in the production of toner 1, except that the dispersion of crystalline polyester resin particles was not added when preparing the dispersion of toner base particles.

[0143] 1-4. Preparation of Toner 28 and Toner 29 Toner 28 and toner 29 were obtained in the same manner as in the production of toner 1, except that the type and amount of the polymerizable monomer added when preparing the dispersion liquid of the binder resin particles was changed as shown in Table 1.

[0144] Table 1 shows the types and amounts (weight ratios relative to the total monomers) of the polymerizable monomer represented by general formula (3), the polymerizable monomer represented by general formula (4) and other polymerizable monomers used in the preparation of toners 1 to 29, the presence or absence of crystalline polyesters (CPEs) added, and the peak molecular weights.

[0145] [Table 1]

[0146] The abbreviations of the polymerizable monomers shown in Table 1 represent the compounds shown in Table 2, respectively.

[0147] [Table 2]

[0148] 2. Evaluation For Toner 1 to Toner 29, the low temperature fixability, adhesion strength, hot offset resistance, and image density unevenness were evaluated by the following methods.

[0149] 2-1.Low temperature fixability The developing device of a commercially available color multifunction printer "bizhub PRO C6500 (manufactured by Konica Minolta Business Technologies, Inc.)" was modified so that the fixing temperature, toner adhesion amount, and system speed could be freely set.

[0150] Under normal temperature and humidity conditions (temperature 20°C, humidity 50% RH), the NPI 128g / m 2 (manufactured by Nippon Paper Industries Co., Ltd.) with a toner adhesion of 11.3 g / m 2 The fixing speed was 300 mm / sec, the temperature of the upper fixing belt was increased from 110°C to 200°C in increments of 5°C, and the temperature of the lower fixing roller was set to 100°C, and solid images were formed in sequence.

[0151] The temperature of the upper fixing belt at which no under-offset occurs when images are successively formed is defined as the minimum fixing temperature. Based on the minimum fixing temperature, the low-temperature fixing property of each toner is evaluated according to the following criteria. A: The minimum fixing temperature was less than 145°C. B: The minimum fixing temperature was 145°C or higher but less than 150°C. C: The minimum fixing temperature was 150°C or higher but less than 155°C. D: The minimum fixing temperature was 155°C or higher.

[0152] 2-2.Adhesive strength Using a commercially available color multifunction printer "bizhub PRESS C107 (manufactured by Konica Minolta, Inc.)," ​​under normal temperature and humidity conditions (temperature 20°C, humidity 50% RH), the A3-sized "OK topcoat paper 157g / m 2 (Oji Paper Co., Ltd.)" with a toner adhesion of 8.0 g / m 2 Five solid images of the above were output in double-sided output mode with the lower roller temperature at 70°C. 500 sheets of evaluation paper without images were placed on top of the output stack of papers and left for two hours. After that, the evaluation paper without images was removed, and the five evaluation papers with images were placed on a flat table. Tape was attached to the tip of the top evaluation paper, and the force required to slowly slide it horizontally was measured with a spring scale. The evaluation papers below the second one from the top were fixed to the table so that they would not move.

[0153] This measurement was repeated four times starting from the top of the evaluation paper, and the average force [N] indicated by the spring balance was taken as the adhesion force. Note that toner with an adhesion force of 2.0 N or less was deemed usable.

[0154] 2-3. Hot offset resistance The developing device of a commercially available color multifunction printer "bizhub PRO C6500 (manufactured by Konica Minolta Business Technologies, Inc.)" was modified so that the fixing temperature could be freely set.

[0155] The evaluation paper used had a basis weight of 128 g / m2 under normal temperature and humidity conditions (temperature 20°C, humidity 50% RH). 2 A solid image with an image density of 0.8 was formed on a thick sheet of paper by increasing the temperature of the upper fixing belt and the lower fixing roller from 120° C. to 220° C. in increments of 10° C.

[0156] When images were successively formed, the hot offset resistance of each toner was evaluated according to the following criteria based on the fixing temperature at which hot offset began to occur. A: No hot offset occurred even at a fixing temperature of 150°C. B: Hot offset occurred at a fixing temperature of 150°C. C: Hot offset occurred at a fixing temperature of 140°C. D: Hot offset occurred at a fixing temperature of 130°C. E: Hot offset occurred when the fixing temperature was less than 130°C.

[0157] 2-4. Image Density Unevenness The developing device of a commercially available color multifunction printer "bizhub PRESS C1100 (manufactured by Konica Minolta, Inc.)" was modified so that the surface temperature of the fixing upper belt could be changed within the range of 140 to 220°C.

[0158] Under normal temperature and humidity conditions (temperature 20°C, humidity 50% RH), the toner adhesion amount was 8.0 g / m on the rough paper "Hammermill tidal (manufactured by Hammermill)" used as the evaluation paper. 2 A solid image was formed at a fixing speed of 460 mm / sec and at a temperature of the upper fixing belt which was 15° C. higher than the temperature of the upper fixing belt at which no under-offset occurred.

[0159] The formed solid image was visually observed for uneven density by trained panelists, and the low-temperature fixing property of each toner was evaluated according to the following criteria. A: No uneven density is observed. B: Slight unevenness in density was observed, but it was determined that this did not affect the quality. C: Density unevenness is clearly visible in some parts of the image, but it is deemed usable. D: Density unevenness is observed throughout the image, and it is deemed unusable.

[0160] The evaluation results are shown in Table 3. Table 3 also shows the peak molecular weight of the acrylic polymer measured during the production of each toner.

[0161] [Table 3]

[0162] As is clear from Table 3, the toner containing an acrylic polymer having a structural unit represented by general formula (1) and a structural unit represented by general formula (2) was able to achieve low-temperature fixing properties, suppression of sticking to other recording media, and reduced hot offset. [Industrial Applicability]

[0163] According to the present invention, there is provided a toner which can form an image which is less likely to stick to other recording media, has excellent low-temperature fixing properties, and is less likely to cause hot offset. [Explanation of symbols]

[0164] 1. Image forming device 10 Heating belt 30 Image processing section 40 Image forming section 41Y, 41M, 41C, 41K Image forming unit 42 Intermediate transfer unit 43 Secondary transfer unit 50 Paper transport section 51 Paper feed section 51a, 51b, 51c Paper feed tray unit 52 Paper output section 52a Paper ejection roller 53 Conveying path section 53a Registration roller pair 60 Fixing device 62 Fixing roller 63 Pressure Roller 70 Image reading unit 71 Paper feeder 72 Scanner 72a CCD sensor 411 Exposure equipment 412 Developing device 413 Electrophotographic photoreceptor 414 Charging device 415 Drum cleaning device 421 Intermediate transfer belt 422 Primary transfer roller 423, 431 Support roller 423A Backup roller 426 Belt cleaning device 426a Elastic members 431A Secondary transfer roller 432 Secondary transfer belt D Manuscript S paper

Claims

1. A toner for developing electrostatic images, the toner base particles of which contain a binder resin, The toner for developing electrostatic images, wherein the binder resin contains a polymer having a constitutional unit represented by the following general formula (1) and a constitutional unit represented by the following general formula (2): 【Chemistry 1】 (In general formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents a hydrocarbon group having 6 to 12 carbon atoms and an alicyclic structure. 【Chemistry 2】 (In general formula (2), R 3 represents a hydrogen atom or a methyl group, R 4 represents a linear or branched hydrocarbon group having 8 to 18 carbon atoms.

2. The toner base particles contain a colorant. The toner for developing electrostatic images according to claim 1.

3. The polymer has a structural unit different from both the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2), The toner for developing electrostatic images according to claim 1.

4. The other structural unit has a structural unit derived from a polymerizable monomer selected from the group consisting of styrene, (meth)acrylic acid, and (meth)acrylic acid esters. The toner for developing electrostatic images according to claim 3.

5. The other structural unit has a structural unit derived from (meth)acrylic acid. The toner for developing electrostatic images according to claim 3.

6. A step of copolymerizing a polymerizable monomer represented by the following general formula (3) and a polymerizable monomer represented by the following general formula (4) to obtain a polymer; forming toner particles comprising the resulting polymer; having A method for producing a toner for developing electrostatic images. 【Chemistry 3】 (In general formula (3), R 1 represents a hydrogen atom or a methyl group, R 2 represents a hydrocarbon group having 6 to 12 carbon atoms and an alicyclic structure. 【Chemistry 4】 (In general formula (4), R 3 represents a hydrogen atom or a methyl group, R 4 represents a linear or branched hydrocarbon group having 8 to 18 carbon atoms.

7. In the step of forming the toner particles, toner particles containing the polymer and a colorant are formed. The method for producing the toner for developing electrostatic images according to claim 6 .

8. The step of obtaining the polymer is a step of obtaining a dispersion of the polymer, the step of forming the toner particles is a step of mixing a dispersion of the polymer; The method for producing the toner for developing electrostatic images according to claim 6 .

9. A step of adhering the toner for developing an electrostatic image according to any one of claims 1 to 5 to a recording medium; a step of fixing the electrostatic image developing toner adhered to the recording medium; The image forming method according to claim 1,

10. An attachment section that attaches the toner for developing electrostatic images according to any one of claims 1 to 5 to a recording medium; a fixing section for fixing the electrostatic image developing toner adhered to the recording medium; An image forming apparatus comprising:

Citation Information

Patent Citations

  • Toner and its production

    JP2000089508A

  • Toner

    JP2014130243A

Cited By

  • Offset printing system with sensors capable of identifying defective products

    KR102838308B1